Implementasi Kepala Sekolah dalam Penguatan Guru menerapkan Nilai-nilai Akidah Akhlaq Melalui Kegiatan Supervisi Akademik di Aliah Candikia - Abdul Rakib; Afifuddin Abdul Jalil; Siti Patimah; Andi Warisno; Nurul Hidayati Murtafiah; A.Gani (STKIP Subang, 2025)
This research aims to describe and obtain empirical data. Empirical data on social media regarding social deviations committed by teachers toward their students, teachers with their colleagues, or teachers with the external social environment, is very interesting for the researcher in conducting a study on the implementation by the principal in strengthening teachers in applying Aqidah and moral values through academic supervision activities at Aliyah Cendikia. This type of research is qualitative descriptive research, which uses an approach involving primary data, secondary data, discussions, interviews, and documentation. The results of this study indicate that there are supporting and inhibiting factors in the principal’s implementation of strengthening teachers in applying Aqidah and moral values. The supporting factor for the implementation of this supervision is that teachers are highly enthusiastic and comprehensive in carrying out activities related to the application of moral values each week. The inhibiting factor is unfavorable weather conditions, such as rain, which causes delays and leads to a less optimal learning situation. The conclusion is that the principal’s implementation in strengthening and applying these values runs optimally, and it is expected that teachers can apply them well within themselves so that noble character and good behavior emerge.